Analysis of Effect of Hemodynamic Parameters on Two-layered Blood Flow in a Mild Stenosed Artery - Timilsina Tripathee, Samundra; Kafle, Jeevan (The Nepali Mathematical Sciences Report, 2023)
Arterial stenosis is the lessening of the arterial wall due to the growth of aberrant tissues that prevent adequate blood flow in the human circulatory system and induces cardiovascular diseases. Mild stenosis, over time, can lead to serious and permanent damage if it remains uncured. Navier-Stokes equation in cylindrical polar coordinates system has been extended by two-layered blood flow along the axial direction with appropriate boundary conditions.A steady flow through a stenosed artery has been investigated extensively using the analytical approach in the case of two-layered blood flow. Mathematical expressions for two-layer hemodynamic parameters such as velocity profile, volumetric flow rate, and effect of stenosis progression on parameters with the variation of core and peripheral layered coefficient of viscosity are derived. Moreover, pressure drop, and shear stress have been calculated analytically in an artery with and without stenosis. Peripheral viscosity has less contribution to varying velocity distribution than the core and is proportional to stenosis size.The volumetric flow rate decreases with an increasing viscosity coefficient. Pressure drop and shear stress attain maximum value in the region stenosis occur maximum height in core layer.The present work could serve as a model in biomedical engineering for the cure of vascular-related diseases and has the potential in designing the devices of this field.